2009
DOI: 10.1016/j.livsci.2008.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Rumen fermentation pattern of dairy heifers fed restricted amounts of low, medium, and high concentrate diets without and with yeast culture

Abstract: Restricted feeding and high concentrate diets are potential strategies for growing dairy heifers. Ruminal manipulation with additives such as Saccharomyces cerevisiae yeast culture (YC) has been shown to alter digestibility when added to this type of diet. An experiment was conducted to investigate the ruminal fermentation and in situ digestibility of diets with 3 different levels of forage to concentrate (F:C) fed at restricted intake without and with YC addition. Three cannulated post-pubertal Holstein heife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
51
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 45 publications
21
51
2
1
Order By: Relevance
“…Optimal ammonia concentration of rumen for rumen microbial activity is more than 4.86 mM (McMurphy et al, 2011). Ammonia concentration found by Lascano & Heinrichs (2009) were lower than 2 mg/dl (5 mg/dL= 3.6 mM), which was the minimal NH 3 -N concentration for microbial growth in rumen. Levels of ammonia produced in this study were 3.9-4.6 mM.…”
Section: Quality Of Diets Based On In Vitro Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…Optimal ammonia concentration of rumen for rumen microbial activity is more than 4.86 mM (McMurphy et al, 2011). Ammonia concentration found by Lascano & Heinrichs (2009) were lower than 2 mg/dl (5 mg/dL= 3.6 mM), which was the minimal NH 3 -N concentration for microbial growth in rumen. Levels of ammonia produced in this study were 3.9-4.6 mM.…”
Section: Quality Of Diets Based On In Vitro Methodsmentioning
confidence: 81%
“…The low ammonia concentration in this study could be related to the low degradability of protein source contained in each ration by microbes to produce ammonia. Protein sources in the rumen, partially can be degraded and cannot be degraded (Lascano & Heinrichs, 2009). The protein can be degraded into amino acids and ammonia, so that the concentration of ammonia is strongly influenced by the protein content in the diet (Lascano & Heinrichs, 2009).…”
Section: Quality Of Diets Based On In Vitro Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same trend was recorded for digestible crude protein (DCP). Addition of Sc to the ration of large animals improved in-vitro DM and OM disappearance and increased in-vivo digestibility of DM, CP and CF [15].…”
Section: Effect Of Yeast On Digestibility and Nutritive Valuesmentioning
confidence: 98%
“…However, some studies found decrease 18 or increase 20 . The response could be associated with the characteristics of the diet.…”
Section: 517mentioning
confidence: 96%